Development of a Multimedia Interactive Learning Package (MILP) for LIS 161 (Computer Based Information System) - Carcellar, Marie Desiree R. (Journal of Philippine Librarianship; Vol 29 No 1 (2009))
Discusses the development of an MILP for LIS 161 and presents the evaluation of the LIS students and LIS IT faculty members on this.
Keywords: multimedia interactive learning package, MILP, LIS 161, systems analysis and design